Translator Knowledge and Skills in the Era of Globalization: A Review Based on Contemporary Research - Silaban, Feni Natasya; Yolanda Zefanya Limbong; Jessica Youevra Ginting; M. Rafif Zaki Ramadhan; Rina Trie Syahputri; Jhon Nicholas Giles (The Explora, 2025)
Modern globalisation has transformed the field of translation, requiring skills that go beyond traditional linguistics. Using frameworks such as the European Master's in Translation (EMT) and literary analysis, this research explores how digital transformation, cultural convergence and market forces have reshaped translator competence. The findings show that translators must maintain strong linguistic foundations while also developing technological proficiency and intercultural mediation skills. Translators now act as cultural bridgebuilders, navigating complex contexts that require specialised knowledge, technological adaptability and market awareness. The study emphasises the importance of interdisciplinary education and adaptable learning in preparing translators for 21st century challenges, highlighting the need for skills such as collaborating with AI program, advanced intercultural communication and adapting multimodal content. The study contributes an updated competency framework that balances technological progress with the human element of translation. Comprehensive professional development strategies are proposed that respect both traditional craftsmanship and innovative methodologies in today's interconnected world.